1978
DOI: 10.1017/s0317167100024690
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Dissection of Cervico-Cerebral Arteries

Abstract: SUMMARY:Sixteen cases of spontaneous dissection of the cervical internal carotid artery (6 verified) are described. The mean age was 45 years. The clinical picture varied from simply headache and a bruit to hemiplegia and aphasia. Eleven patients had transient ischemic attacks. Headache, facial pain, a subjective bruit, oculo-sympathetic palsy and transient monocular blindness were present in various combinations in two-thirds of cases and their presence suggested the correct diagnosis. Examples of suspected d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
22

Year Published

1979
1979
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(109 citation statements)
references
References 8 publications
2
85
0
22
Order By: Relevance
“…As reported previously [6,9,13,27,38], stroke and TIA were the most common presenting features in our study affecting 86 % of patients without a significant difference between CAD and VAD.…”
Section: Discussion S Clinical Findingssupporting
confidence: 85%
See 1 more Smart Citation
“…As reported previously [6,9,13,27,38], stroke and TIA were the most common presenting features in our study affecting 86 % of patients without a significant difference between CAD and VAD.…”
Section: Discussion S Clinical Findingssupporting
confidence: 85%
“…Chiropractic manipulation of the cervical spine was performed prior to the diagnosis of dissection in 20 (16 %) patients, of whom 5 had CAD, 14 had VAD and one had both CAD and VAD (p < 0.01 for CAD versus VAD). The onset of symptoms occurred immediately after the procedure in (13) or death (%) * p < 0.01 for the comparison of CAD and VAD; "vascular findings" refer to a total of 85 affected carotid arteries and 60 affected vertebral arteries twelve patients and within two to ten days in the remaining eight patients.…”
Section: S Risk Factorsmentioning
confidence: 99%
“…Yamaura et al [169] found that such neurological deficits were commonly seen when the aneurysm was located within 10 mm of the midline or more than 13 mm posterior to the clivus. Thrombosis of the VA and its perforators to the medulla is known to play a more important role in the development of lateral medullary infarction than thrombosis of the PICA [21]. When the PICA is a major supplier of blood to the medulla, the PICA should remain patent proximal to the clip.…”
Section: Complications and Their Avoidancementioning
confidence: 99%
“…Catheter-angiography has traditionally been the gold standard for the diagnosis of extracranial carotid and vertebral dissection [59,60]. Dissections are commonly classified as stenotic, occlusive, or aneurysmal, with dissecting aneurysms occurring in 25-50% of patients with internal carotid artery involvement [28,61,62].…”
Section: Diagnosismentioning
confidence: 99%